Specifics of the professional-pedagogical motivation in pedagogical research instrument in pedagogical activity. - Stepanchenko N.I (Kharkov National Pedagogical University, 2012)
The analysis of methods of estimation is presented to professionally-pedagogical motivations and general and concrete possibilities of their realization are certain in pedagogical diagnostics. The groups of methods of collection of diagnostic information are selected about motivation. It is demonstrated that the evaluation of pedagogical activity motivation can be enacted only with the help of economical and objective, direct and indirect diagnostic methods, which demonstrate considerable constructive validness. When choosing the practical diagnostic method, it is suggested that it is based on individual, systemic and conceptual principles. The individual-activity approach is based on research of the personality in the study-cognitive process activity. The system principle assumes the research of professional-pedagogical motivation components are according to a unified system. The principle of conceptuality demands complexity, unity and logical non-contradiction of approaches and evaluations of diagnostic results.